REPRESENTATION OF LOCAL CULTURE AND ORGANIZATION IN BANK OFFICE ARCHITECTURE FOR PUBLIC SERVICE INNOVATION - Dewi, Ni Made Emmi Nutrisia; Prasiani, Ni Komang; Rahayu, Ni Komang Desita (E-Journal of Cultural Studies; Vol 17 No 3 (2024): Volume 17 Number 3 August 2024, 2024)
In the era of globalization, the integration of local cultural elements into modern architecture is becoming increasingly important to maintain cultural identity. Bali, with its rich culture and architectural traditions, offers a variety of elements that can be adapted to enhance the aesthetics and functionality of modern buildings, including bank offices. The main focus of this study is to analyze how Balinese organizational values ??and cultural heritage are reflected in the physical design of bank offices, including layout, building materials, and architectural ornaments to enhance customer interaction and service creativity. The research methods used include a qualitative approach, case studies of bank offices in Bali, field observations, and interviews with architects, bank employees, and customers. The results show that cultural integration in the architectural design of bank offices can strengthen corporate identity, enhance customer experience and interaction, and encourage service innovation. In conclusion, this study emphasizes the importance of considering cultural aspects and organizational values ??in architectural design as an effective way to create an environment that supports service innovation and enriches customer experience and also contributes to cultural preservation. These findings confirm that architecture that reflects organizational culture and local traditions can be an innovative strategy to improve the image and competitiveness of banks in the era of globalization. Keywords : representation, architecture, culture, Bali, organization, office, bank, service, public